Faculty Development for Christian Mission: The State of the Field. Issue 5 (27th September 2022) - Cockle, Theodore F.; Glanzer, Perry L.; Whitmore, Madeline
Abstract: Scholars studying Christian higher education frequently suggest that faculty are the campus constituents with the most influence over the future of an institution's Christian mission. Thus, both faculty hiring and development are important elements for maintaining and strengthening the Christian identity of a university over time. Despite this importance, we do not know of a study that has surveyed the missional faculty-development processes of Christian colleges and universities. We utilized a survey research design to determine how Christian institutions educate faculty to integrate their Christian mission into their teaching, scholarship, and institutional service. We found that institutions tended to offer introductory trainings and workshops early in the career of faculty. After these early programs, the most effective faculty development resources identified were the conversations facilitated through discipline-specific academic journals and professional organizations. Moving forward, the institutions from which we heard hoped for increased resources and institutional prioritization for these conversations, especially at the advanced and senior faculty level. In conclusion, we suggest four opportunities for practical innovation to ensure future growth and engagement of faculty development for Christian mission: include a proactive approach to hiring practices, place a renewed emphasis on Christ-animated scholarship, continue to expand the conversation beyond the humanities, and introduce programming and incentives aimed at engaging senior faculty.